Automation of measurements of photoelectric parameters of focal solar modules - Kozyr, M. (ХНУРЕ, 2020)
In this paper, development of a software module to automate the measurements of photovoltaic parameters of a silicon focal solar module is discussed. The analysis of existing analogues allowed to clearly define the main characteristics that the automatization module should have. As a result, a PC interface that is connected to the module was developed, created a general view of the circuit board and calculated the reliability. The developed software allows to control the basic parameters of the solar module.
Keywords: solar module; automation; reliability; software